Keuntungan Investasi Bitcoin dalam Prespektif Tingkat Investasi: Studi Empiris di Amerika Periode 2019-2023 - Purbasari, Heppy; Prasetyo, Anggo (Benefit: Jurnal Manajemen dan Bisnis, 2025)
This study analyzes the effect of inflation, interest rates, and money supply (M2) on Bitcoin returns, with investment level as a moderating variable, in the context of the United States economy during 2019–2023. Using a quantitative approach, this research employs multiple linear regression and Moderated Regression Analysis (MRA) based on 60 monthly observations. Data were obtained from FRED, TradingView, and Grayscale Bitcoin Trust (GBTC). The findings show that inflation has a significant negative effect on Bitcoin returns, while interest rates and money supply have no significant effect. Investment level moderates the relationship between inflation and Bitcoin returns negatively, but does not moderate the effect of interest rates and M2. These results indicate that institutional investment plays a selective role in shaping the relationship between macroeconomic factors and Bitcoin. The study offers implications for investors and policymakers in digital asset management.